2011
DOI: 10.3233/jad-2011-110512
|View full text |Cite
|
Sign up to set email alerts
|

Therapeutic Potential and Anti-Amyloidosis Mechanisms of Tert-Butylhydroquinone for Alzheimer's Disease

Abstract: Alzheimer’s disease (AD) is a major cause of dementia in the elderly with no effective treatment. Accumulation of amyloid-β peptide (Aβ) in the brain, one of the pathological features of AD, is considered to be a central disease-causing and disease-promoting event in AD. In this study, we showed that feeding male AβPP/PS1 transgenic mice, a well established mouse model of AD, with a diet containing phenolic antioxidant tert-butylhydroquinone (TBHQ) dramatically reduced brain Aβ load with no significant effect … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
28
0
1

Year Published

2012
2012
2023
2023

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 40 publications
(30 citation statements)
references
References 63 publications
1
28
0
1
Order By: Relevance
“…Concentrations of urea in BALF and in the plasma were measured using a commercially available kit (Teco Diagnostics, Anaheim, CA) and the dilution factors of epithelial lining fluid (ELF) were calculated based on urea concentrations in the plasma and in BALF, which were used to normalize the antioxidant concentrations in ELF. Total GSH contents in lung tissue were measured using a recycling assay as we have described previously [42]. The protein contents were measured by a BCA kit and GSH concentrations calculated based on standard curve run together with the samples and normalized by protein content.…”
Section: Methodsmentioning
confidence: 99%
“…Concentrations of urea in BALF and in the plasma were measured using a commercially available kit (Teco Diagnostics, Anaheim, CA) and the dilution factors of epithelial lining fluid (ELF) were calculated based on urea concentrations in the plasma and in BALF, which were used to normalize the antioxidant concentrations in ELF. Total GSH contents in lung tissue were measured using a recycling assay as we have described previously [42]. The protein contents were measured by a BCA kit and GSH concentrations calculated based on standard curve run together with the samples and normalized by protein content.…”
Section: Methodsmentioning
confidence: 99%
“…Gp91ds-tat, a Nox2 inhibitory peptide, decreased both oxidative stress and AD pathology in aged mice [59]. Also, It has been recently shown that feeding AβPP/PS1 double transgenic mice, a mouse model of AD, with a diet containing phenolic antioxidant tert-butylhydroquinone, inhibits Nox2 protein expression and suppressed lipid peroxidation in the cerebral cortex and hippocampus [60]. It was also found that age-dependent increases of Aβ had a significant linear relationship with both Nox4 activity and cognitive performance in “humanized” APP×PS1 knock-in mice [61].…”
Section: Nox and Alzheimer’s Diseasementioning
confidence: 99%
“…Previous studies have shown that tBHQ exerts protective effects in multiple neurodegenerative conditions, including stroke (Shih et al, 2005), traumatic brain injury (Jin et al, 2011;Lu et al, 2014), Parkinson's disease (Hara et al, 2003), and Alzheimer's disease (Eftekharzadeh et al, 2010;Akhter et al, 2011). However, the underlying mechanisms of tBHQ's protective role have not been elucidated.…”
Section: Introductionmentioning
confidence: 98%